Extension of sperm motility leads to increased rates of fertilization and hatching in curimba, Prochilodus lineatus. (19th June 2013) - Hernández Cuadrado, E. E.; Solis Murgas, L. D.; de, V.; Rodrigues Ferreira, M.; de, E.
Summary The objective of this study was to evaluate the effects of six activating solutions on duration of sperm motility, fertilization rate (FR), and hatching rate (HR) of Prochilodus lineatus (Valenciennes, 1837). The activating solutions (SA) used were: SA0 (199 mOsm kg−1, pH 8.5), SA1 (138 mOsm kg−1, pH 7.5), SA2 (256 mOsm kg−1, pH 7.5), SA3 (131 mOsm kg−1, pH 10), NaCl (92 mOsm kg−1, pH 7.5) and distilled water (32 mOsm kg−1, pH 7.5). SA1 induced the highest motility, FR and HR, compared with the other activating solutions. The lowest motility was obtained with SA0, with no fertilization or hatching, whereas motility was zero with SA2 and SA3. It is possible to conclude that the solution SA1 can be used for the activation of gametes during fertilization in induced reproduction of curimba to achieve higher fertilization and hatching rates. Thus, it was found that the osmolality and pH of activating solutions, probably with the participation of dissolved substances therein, are the main factors acting on semen motility after activation.